HASIL BELAJAR MENDESAIN KEBAYA MODIFIKASI DENGAN METODE COPY THE MASTER PADA SISWA KELAS XI TATA BUSANA SMK NEGERI 3 TEBING TINGGI - Hanim, Halida; Azhari, Ika Wahyu (Universitas Negeri Medan, 2014)
ABSTRACT This study aims to determine grade XI students results dressmaking SMK Negeri 3 Tebing Tinggi on kebaya modification design method by using the master method. This study used a descriptive method. The population in this study were 73 students of grade XI dressmaking students of SMK Negeri 3 Tebing Tinggi. Purposive sampling technique was used, so the number of sample is 25 students. The instrument used in this study is the assessment sheet distributed to five observers with assessment indicators containing grains statements relating to results of kebaya design modifications are seen as a whole. To determine the validity of the observation sheet test observer agreement. Based on the test results show that the trend of learning outcomes kebaya modifications design with the master copy method to design 1: Nt = 87, Nr = 36, M = 60, SD = 11 with less category (96%), design 2: Nt = 88, Nr = 34, M = 67, SD = 12 with less category (72%), design 3: Nt = 93, Nr = 34, M = 74, SD = 14 with less category (44%), design 4: Nt = 94, Nr = 50, M = 59, SD = 9 with less category (60%), design 5: Nt = 98, Nr = 48, M = 70, SD = 12 with less category (72%), 6 designs: Nt = 92, Nr = 59, M = 78, SD = 11 in both categories (40%), design 7: Nt = 99, Nr = 55, M = 79, SD = 14 with the excellent category (44%) and design 8: Nt = 100, Nr = 55, M = 88, SD = 11 with the excellent category (60%). It can be concluded that the results of kebaya modifications design with copy the master method can improve students™ achievement in kebaya design on dressmaking grade XI students of SMK Negeri 3 TebingTinggi. Kata Kunci : Desain kebaya, copy the master .